2012
DOI: 10.1155/2012/248082
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation and Passive Flow Control of a Cavitating Centrifugal Pump

Abstract: Passive flow control techniques are used to improve the flow field and efficiency of centrifugal pumps and turbomachines, in general. An important phenomenon that mechanical engineers have to take into account is cavitation. It leads to the decrease of the pump performance and total head. In the present experimental study, a centrifugal pump is investigated in cavitating conditions. A passive flow control is realized using three different blade leading edge angles in order to reduce the cavitation development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Results indicate that a significant delay in cavitation inception could be achieved. 123, 124 Kyparissis and Margaris 125,126 worked on different centrifugal pump blade designs, including double-arc synthetic blades and different blade leading edge angles. The investigation considered pump hydraulic performance and cavitation in tandem.…”
Section: B Blade Profile and Geometry Modificationmentioning
confidence: 99%
“…Results indicate that a significant delay in cavitation inception could be achieved. 123, 124 Kyparissis and Margaris 125,126 worked on different centrifugal pump blade designs, including double-arc synthetic blades and different blade leading edge angles. The investigation considered pump hydraulic performance and cavitation in tandem.…”
Section: B Blade Profile and Geometry Modificationmentioning
confidence: 99%
“…Passive control of hydrofoil cavitation refers to disturb the flow by changing the surface structure or material properties of hydrofoils, so as to inhibit the occurrence and development of cavitation [15] , [16] . There are many studies on the passive control methods, such as setting obstacles on the hydrofoil surface [17] , [18] and modifying the airfoil profiles [19] , [20] . Lin et al [17] found that circular obstacles on the plane hydrofoil could stabilize the leading-edge cavitation and reduce the shedding cavitation.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Leighton et al has proven that acoustic data not only aids in cavitation detection and pump condition monitoring but also allows for estimations of cavitation scale and bubble population within a liquid [15]. Finally, deep learning techniques, including novel and improved CNN models, have demonstrated enhanced reliability in diagnosing deviations in pump operation [16] and piping leakage [17] using acoustic data…”
Section: Introductionmentioning
confidence: 99%
“…Detecting the cavitation phenomenon and determining its occurrence window in centrifugal pumps is crucial for both preventive maintenance and the optimal design of mechanical components such as blades. Kyparissis and Margaris have investigated the effects of design parameters on cavitation formation and the overall performance of centrifugal pumps, emphasizing the importance of understanding where and how cavitation occurs in different pump designs [16,23].…”
Section: Introductionmentioning
confidence: 99%